Extracorporeal Co2 Removal in Hypercapnic Patients At Risk of Noninvasive Ventilation Failure: A Matched Cohort Study With Historical Control*. Issue 1 (January 2015) - Del Sorbo, Lorenzo; Pisani, Lara; Filippini, Claudia; Fanelli, Vito; Fasano, Luca; Terragni, Pierpaolo; Dell'Amore, Andrea; Urbino, Rosario; Mascia, Luciana; Evangelista, Andrea; Antro, Camillo; D'Amato, Raffaele; et al.
Abstract : Objectives: To assess efficacy and safety of noninvasive ventilation-plus-extracorporeal Co2 removal in comparison to noninvasive ventilation-only to prevent endotracheal intubation patients with acute hypercapnic respiratory failure at risk of failing noninvasive ventilation. Design: Matched cohort study with historical control. Setting: Two academic Italian ICUs. Patients: Patients treated with noninvasive ventilation for acute hypercapnic respiratory failure due to exacerbation of chronic obstructive pulmonary disease (May 2011 to November 2013). Interventions: Extracorporeal CO2 removal was added to noninvasive ventilation when noninvasive ventilation was at risk of failure (arterial pH ⩽ 7.30 with arterial PCO2 > 20% of baseline, and respiratory rate ≥ 30 breaths/min or use of accessory muscles/paradoxical abdominal movements). The noninvasive ventilation-only group was created applying the genetic matching technique (GenMatch) on a dataset including patients enrolled in two previous studies. Exclusion criteria for both groups were mean arterial pressure less than 60 mm Hg, contraindications to anticoagulation, body weight greater than 120 kg, contraindication to continuation of active treatment, and failure to obtain consent. Measurements and Main Results: Primary endpoint was the cumulative prevalence of endotracheal intubation. Twenty-five patients were included in the noninvasive ventilation-plus-extracorporeal CO2 removal group. The GenMatch identified 21 patients for the noninvasive ventilation-only group. Risk of being intubated was three times higher in patients treated with noninvasive ventilation-only than in patients treated with noninvasive ventilation-plus-extracorporeal CO2 removal (hazard ratio, 0.27; 95% CI, 0.07–0.98; p = 0.047). Intubation rate in noninvasive ventilation-plus-extracorporeal CO2 removal was 12% (95% CI, 2.5–31.2) and in noninvasive ventilation-only was 33% (95% CI, 14.6–57.0), but the difference was not statistically different ( p = 0.1495). Thirteen patients (52%) experienced adverse events related to extracorporeal CO2 removal. Bleeding episodes were observed in three patients, and one patient experienced vein perforation. Malfunctioning of the system caused all other adverse events. Conclusions: These data provide the rationale for future randomized clinical trials that are required to validate extracorporeal CO2 removal in patients with hypercapnic respiratory failure and respiratory acidosis nonresponsive to noninvasive ventilation. Abstract : Supplemental Digital Content is available in the text.